Peningkatan Kompetensi Penerjemahan Arab–Indonesia dan Penulisan Karya Ilmiah melalui Program Pendampingan di Pondok Kreatif Baitul Kilmah: Pengabdian - Nuruddin, Alfy Mamduh; H, Harisman; Mulyanto, Dedi; Samsirin, Samsirin; TH, M. Afif Fauzi; Sulthan, Muhammad Rafi (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This community service program aims to improve the Arabic–Indonesian translation competence and academic writing skills of fourth-semester students of the Arabic Language Education Department at the University of Darussalam Gontor. The main challenges addressed in this activity involve students’ limited understanding of translation theories and strategies, as well as their difficulties in producing academic articles that meet scholarly standards. To address these issues, a mentoring program was conducted at Pondok Kreatif Baitul Kilmah with the participation of 27 students. The implementation consisted of four sessions, each lasting two hours, including workshops on translation theory, practical exercises in translating Arabic texts into Indonesian, mentoring on scientific writing, and presentation of students’ work. Evaluation was carried out through task assessments during the mentoring process and feedback from the instructor. The findings indicate that the program contributed to enhancing students’ ability to comprehend Arabic texts, select accurate lexical equivalents, and develop coherent academic paragraphs that align with standard scientific writing conventions. Therefore, this mentoring program is considered effective in strengthening students’ academic competencies in translation and scientific writing.